Kagen the damned - Maberry, Jonathan ([Kagen the damned, 2022)
"Kagen the Damned marks the first installment of an exciting new series of dark epic fantasy novels from bestselling author Jonathan Maberry. Sworn by Oath Kagen Vale is the trusted and feared captain of the place guard, charged with protection the royal children of the Silver Empire. But one night, Kagen is drugged and the entire imperial family is killed, leaving the empire in ruins. Abandoned by the Gods Haunted and broken, Kagen is abandoned by his gods and damned forever. He becomes a wanderer, trying to take down as many of this enemies as possible while plotting to assassinate the usurper -the deadly Witch-king of Hakkia. While all around him magic -look banished from the world-returns in strange and terrifying ways. Fueled by Rage To find the royal children and exact his vengeance, Kagen must venture into strange lands, battle bizarre and terrifying creatures, and gather allies for a suicide mission into the heart of the Witch-king's empire. Kings and gods will fear him. Kagen the Damned"--